Preliminary development of lapachol gel: in vitro permeation study (Revista Brasileira de Ciências Farmacêuticas, 2004)
The scope of this work was to develop two gel formulations containing lapachol, substance with known anti-inflammatory activity. In order to achieve a more effective topical delivery, the effects of vehicles and enhancers were evaluated. The influence of the Carbopol® resin (934P, 940 and 941), the pH of the formulation (5, 7 and 8), the concentration of the active (0.2%, 0.5% and 1.0%) and the incorporation of Tween® 80 were investigated. A series in vitro permeation studies were conduct in classical Franz-type diffusion cells using Durapore® synthetic membranes and Wistar mouse skins as barriers. Through the careful analyse of the data obtained, we could observe that the addition of Tween® 80 leads to a significant increase in the in vitro diffusion of the active, except for the formulations containing Carbopol® 934P and 0.2% of lapachol. The formulations assayed presented best in vitro diffusion rates of lapachol at pH 8 when 0.5% or 1.0% of the active was added. However, the preparations containing 1.0% of drug presented little insoluble crystals of lapachol.